A Randomized Controlled Trial of a Nurse-Led Supportive Care Package (SurvivorCare) for Survivors of Colorectal Cancer. (15th June 2016) - Jefford, Michael; Gough, Karla; Drosdowsky, Allison; Russell, Lahiru; Aranda, Sanchia; Butow, Phyllis; Phipps-Nelson, Jo; Young, Jane; Krishnasamy, Mei; Ugalde, Anna; King, Dorothy; Strickland, Andrew; et al.
Abstract : Introduction: Colorectal cancer (CRC) and its treatments can cause distressing sequelae. We conducted a multicenter randomized controlled trial aiming to improve psychological distress, supportive care needs (SCNs), and quality of life (QOL) of patients with CRC. The intervention, called SurvivorCare (SC), comprised educational materials, needs assessment, survivorship care plan, end-of-treatment session, and three follow-up telephone calls. Methods: At the end of treatment for stage I–III CRC, eligible patients were randomized 1:1 to usual care (UC) or to UC plus SC. Distress (Brief Symptom Inventory 18), SCNs (Cancer Survivors' Unmet Needs measure), and QOL (European Organization for Research and Treatment of Cancer [EORTC] QOL questionnaires C30 and EORTC CRC module CR29) were assessed at baseline and at 2 and 6 months (follow-up 1 [FU1] and FU2, respectively). The primary hypothesis was that SC would have a beneficial effect on distress at FU1. The secondary hypotheses were that SC would have a beneficial effect on (a) SCN and QOL at FU1 and on (b) distress, SCNs, and QOL at FU2. A total of 15 items assessed experience of care. Results: Of 221 patients randomly assigned, 4 were ineligible for the study and 1 was lost to FU, leaving 110 in the UC group and 106 in the SC group. Patients' characteristics included the following: median age, 64 years; men, 52%; colon cancer, 56%; rectal cancer, 35%; overlapping sites of disease, 10%; stage I disease, 7%; stage II, 22%; stage III, 71%. Baseline distress and QOL scores were similar to population norms. Between-group differences in distress at FU1 (primary outcome) and at FU2, and SCNs and QOL at FU1 and FU2 were small and nonsignificant. Patients in the SC group were more satisfied with survivorship care than those in the UC group (significant differences on 10 of 15 items). Conclusion: The addition of SC to UC did not have a beneficial effect on distress, SCNs, or QOL outcomes, but patients in the SC group were more satisfied with care. Abstract : This trial aimed to improve psychological distress, meet supportive care needs, and enhance quality of life of patients with colorectal cancer. SurvivorCare (SC) comprised educational materials, needs assessment, a survivorship care plan, an end-of-treatment session, and follow-up telephone calls. Patients were followed up at 2 and 6 months. Adding SC to usual care did not have a beneficial effect on outcome measures, but patients in the SC group were more satisfied with care.